Pengaruh Penggunaan Perturb & Observe pada MPPT terhadap Daya Keluaran Sel Surya - Ernando Rizki Dalimunthe; Freddy Kurniawan; Lasmadi Lasmadi (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2019)
Optimizing the output power value of a solar cell requires a tracker. The tracking is called the maximum power point tracking (MPPT) which will produce a maximum output power value. Each component in this system is modeled into Simulink. This simulation is designed to optimize the work of solar cells by searching maximum power points using perturb and observe (P&O) algorithms, then duty cycles are output of the algorithms become Buck-Boost Converter inputs as switching so they can produce output power with better output power. Simulation results show that MPPT can increase the average output power on changes in the value of sun irradiation, temperature and load than systems that do not use MPPT. The factor of the average difference in power is 37.82%.